If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 78 + -15(q + x) = 3q 78 + (q * -15 + x * -15) = 3q 78 + (-15q + -15x) = 3q Solving 78 + -15q + -15x = 3q Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Add '-3q' to each side of the equation. 78 + -15q + -3q + -15x = 3q + -3q Combine like terms: -15q + -3q = -18q 78 + -18q + -15x = 3q + -3q Combine like terms: 3q + -3q = 0 78 + -18q + -15x = 0 Add '-78' to each side of the equation. 78 + -18q + -78 + -15x = 0 + -78 Reorder the terms: 78 + -78 + -18q + -15x = 0 + -78 Combine like terms: 78 + -78 = 0 0 + -18q + -15x = 0 + -78 -18q + -15x = 0 + -78 Combine like terms: 0 + -78 = -78 -18q + -15x = -78 Add '15x' to each side of the equation. -18q + -15x + 15x = -78 + 15x Combine like terms: -15x + 15x = 0 -18q + 0 = -78 + 15x -18q = -78 + 15x Divide each side by '-18'. q = 4.333333333 + -0.8333333333x Simplifying q = 4.333333333 + -0.8333333333x
| 78-15(q+x)=2x | | 5x^2-21=10x | | 38x+3= | | 78-30q=32x | | 2x+7= | | 40x=80 | | -13-g=37+9g | | 2x+7+38x+3= | | 12m^2+7m= | | 4b+23=23-4b | | 4x+2=20-2x | | 4(x-6)+2=6(x+2)-6 | | 0=3k^2+k^3 | | 4a+3b=t | | 70=10(5y+2) | | 4.2x-10.05=6.3-6.7x | | 21x-8-18x+3=16x-3-13x+15 | | X+8=23 | | 4h^2-12+8=0 | | 6(4r+5)=-3(6r+14) | | 12x^3+2x^2-30x-5=0 | | 132-2x=6x+20 | | 6x-3x^2=-12 | | -10-4x=14-8x | | 32+j=59 | | 20x^2=-4x | | 4=b-39 | | 5+8x=68+x | | 100=13+h+2+5 | | 13v=169 | | 61=z-7 | | 150=15c |